Improving the learning activities by implementing the scientific approach through discovery learning model - Kuswati, Eni (Dinamika Pendidikan, 2016)
The objectives of the study were to describe the planning, implementation, observation and reflection, to evaluate and identify the constraints and solutions at each cycle and also to find out the learning outcomes achieved with scientific approach through the discovery learning model for 2nd grade students at SMP 2 Kudus. It was a descriptive qualitative study. The research result showed that the studentsâ activity was enough on the first cycle and good on the second cycle. The average mean score of the written test on the first first cycles B- and A- on the second cycle. If it was seen from the minimum completeness criterion (KKM), there were 19 students with the percentage of acquisition was 55% on the 1st cycle and there were 32 students with the percentage of acquisition was 93% on the 2nd cycle. The observation results showed that scientific approach gave improvement of studentsâ activities on the first cycle and the second cycle. The results obtained from the use of scientific approach through the discovery learning model to improve the activity was good, but it needs to be observed continuously on studentsâ attitudes, skills and knowledge in school life.Penelitian ini bertujuan untuk mendeskripsikan Perencanaan,Â  Pelaksanaan, observasi dan refleksi serta mengevaluasi, mengidentifikasi kendala dan solusi dalam mengatasi kendala tiap siklusnya serta mengetahui hasil yang dicapaiÂ  dalam pembelajaranÂ  pendekatan scientific melalui model Discovery Learning pada peserta didik kelas VII E di SMP 2 Kudus. Bentuk penelitian ini adalah deskriptif kualitatif. Hasil penelitian bedasarkan pada siklus I tingkatÂ  aktivitas peserta didik menunjukanÂ  rata-rata capaian optimum cukup, pada siklus II tingkat aktivitas peserta didik menunjuka rata-rata capaian optimum Baik. Perolehan rata-rata skor rerata Â tes tertulis pada siklus I adalahÂ  B- danÂ  pada siklus II rata-rata skor rerata adalah A-. Apabila dilihat dari Kriteria Ketuntasan Minimal (KKM) hasil peserta didik pada siklus 1 yang mencapai KKM sebanyak 19 peserta didik dengan presentase perolehan 55% dan pada siklus ke II peserta didik yang mencapai KKM sebanyak 32 peserta didik dengan perolehan presentase sebanyak 93 %. Hasil observasi pembelajaran pendekatan scientific pada siklus I dan Siklus II terhadap Aktivitas Â guru menunjukkan adanya peningkatan. Hasil yang diperoleh dari penggunaan pendekatan scientific melalui model Discovery Learning dalam upaya peningkatan aktivitas sudah baik, namun perlu dibarengi dengan pengamatan yang berkesinambungan terhadap sikap, keterampilan dan pengetahuan peserta didik dalam kehidupan di sekolah.